The organizational structures for community-based natural resources management in Southern Africa - Campbell, Bruce M.; Shackleton, S. (2001)
Throughout Southern Africa there has been a move to decentralize natural resource management (NRM). Decentralization has taken many forms, resulting in different organizational structures for NRM. Fourteen case studies from eight countries can be classed into four types, depending on the key organizations for NRM: (1) district-level organizations; (2) village organizations supported by sectoral departments (e.g. Village Forest Committees); (3) organizations or authorities outside the state hierarchy (e.g. traditional authority, residents’ associations), and (4) corporate organizations at the village level (e.g. Trusts, conservancies, property associations). Attitudes towards district-level schemes amongst local people are generally negative. The greater the authority village organizations receive the more likely they are to succeed. In the cases with corporate organizations, local residents have received user or proprietary rights over resources. Such cases reflect the best chances of community-based natural resources management (CBNRM) being successful. It is clear that policies that explicitly decentralize authority to village-level organizations help to avoid some of the problems that have emerged. The impact of private sector stakeholders can be positive or negative depending on the institutional arrangements in place. Many of the cases have demonstrated the key role that external facilitation plays in building the capacity of local organizations. Traditional leaders have continued to play a role in NRM, with varying degrees of authority and control. The paper ends with a discussion of the key features for the success of CBNRM